2020
DOI: 10.1007/s00586-020-06525-1
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip strength correlates with walking in lumbar spinal stenosis

Abstract: Purpose To examine the relationship between handgrip strength and leg extension power, walking speed, and intermittent claudication for lumbar spinal stenosis (LSS) using computed tomography. Methods We examined patients who underwent laminectomy for LSS from June 2015 through March 2018. Before spine surgery, we evaluated walking distance, handgrip strength, leg extension power (LEP), 10-m walk test (time and steps), psoas muscle index (PMI), and the area of both total and multifidus muscle using plain comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Two of these studies also showed no significant association between other objectives measures and walking capacity ( 36 , 40 ). Finally, one study reported a moderate negative correlation between handgrip strength and walking time and a weak positive correlation between handgrip strength and walking distance ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two of these studies also showed no significant association between other objectives measures and walking capacity ( 36 , 40 ). Finally, one study reported a moderate negative correlation between handgrip strength and walking time and a weak positive correlation between handgrip strength and walking distance ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…They also reported weak associations between either trunk extensor muscle endurance, knee flexion ROM, or knee extension strength asymmetry and the Habitual Gait Speed test, and a weak association between leg strength and the Chair Stand test ( 39 ). Finally, one study reported a moderate negative correlation between handgrip strength and walking steps ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lifestyle interventions in the elderly, especially exercise and nutrition, have become the mainstay of treatment to improve this low muscle strength. These operations are also preventive measures for the elderly requiring long-term care, which are faced by countries entering a superaging society.There are many evaluation items based on grip strength [7][8][9], but few studies have evaluated handgrip endurance (ED) [10]. In addition, there are no studies that measured and compared the difference in ED changes between the elderly and young people, and the change with elapsed time (seconds).…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest an article titled "Handgrip strength correlates with walking in lumbar spinal stenosis" authored by Inoue et al [1]. They examined the relationship between handgrip strength and leg extension power, walking speed, and intermittent claudication for lumbar spinal stenosis (LSS).…”
mentioning
confidence: 99%